OPERATION DOWNUNDER - Mozingo, R.L.; Lewis, R.J.; Kloepfer, W. (Tufts Archival Research Center, 2007)
Confidential; Reponse to Tobacco Institute (TI) Executive Committee Operation Downunder proposal. Plans to deal with the perception of the tobacco industry, public smoking, the social perception of smokers, and government intervention in smoking regulation. Believes operation must be more fully explored and research before its implementation. Lists key objectives/premises of operation. Comments on strategy and implementation. Recommends pursuing some parts of the operation but being cautious about others.